Fields of perturbation of pressure, density and speeds at a geostrophic state of atmosphere - A. A. Fedina; A. S. Mkrtchyan; A. I. Shevchenko; N. A. Shatalov (Наука. Инновации. Технологии, 2022)
Introduction: Fields of perturbation of pressure, density and speeds at a geostrophic state of atmosphere The general (global) atmospheric circulation (OCA) is understood as the totality of air currents (winds), which is the horizontal extent (scale), which allows you to get the size of the material and the oceans. Airflow systems such as westerly transport in temperate latitudes of both hemispheres, trade winds of subtropics, monsoons, string currents, a system of motion in planetary waves, cyclones and anticyclones. Atmospheric circulation is determined by a number of factors that are unevenly distributed across the globe and the Coriolis force. As is known, the geostrophic state of the atmosphere is its basic stationary state. In this case, the pressure perturbation field remains unknown to us. Therefore, in this situation, proceed as follows: the actual pressure field determines the speed of the geostrophic wind. It turns out that the geostrophic state is uncertain. In this paper, a solution is proposed for pressure and density perturbation ields corresponding to the geostrophic (stationary) state of the atmosphere. Results of the research: for pressure and density perturbations we get: P--2a>0zPe ,0 Ak\\x+k2y\\ p'=0=^=pe *2--а(УА"У)(*1Лг+М From here for the projections of the speed of the geostrophic wind we obtain the expression 1 dp' 12m0zPe ф2+к2c°0zPe dx ф2+к2 Discussion and conclusion: Thus, the analysis of the linearized system of equations of atmospheric dynamics is carried out. This system includes the equations of motion in three projections on the coordinate axes, the continuity equation and the heat equation. It is shown that the zero vertical component of the velocity is a consequence of the stationar-ity of the temperature perturbation. As a rule, this fact is simply postulated and is included in the definition of the